Combustion Efficiency and Emission Control of Alternative Fuels: A Comprehensive Review - Seto, Dewandono Bayu (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2025)
The growing demand for clean and efficient energy sources has driven the development of various alternative fuels to replace fossil fuels, which continue to dominate the transportation and industrial sectors. This article presents a comprehensive review of the combustion and emission characteristics of four major types of alternative fuels: bioethanol, biodiesel, biogas, and hydrogen. The review is based on selected scientific literature published between 2020 and 2024, with a focus on thermal efficiency, emission profiles (CO, HC, NOₓ, PM), and relevant emission control technologies. The analysis shows that each fuel exhibits unique characteristics in terms of combustion performance and emission behavior. Hydrogen offers the highest thermal efficiency and zero carbon emissions but requires specialized combustion and storage systems. Bioethanol and biodiesel are relatively compatible with conventional engines, though they face technical limitations and risks of secondary emissions. Biogas demonstrates high potential, particularly when upgraded to biomethane. This study also highlights the importance of integrating fuel selection with appropriate emission control strategies. The findings are expected to serve as a strategic reference for the development of sustainable energy systems in the automotive and industrial sectors